Integrative Analysis of Nanopore and Illumina Sequencing Reveals Alternative Splicing Complexity in Pig Longissimus Dorsi Muscle - Shu, Ze; Wang, Ligang; Wang, Jinbu; Zhang, Longchao; Hou, Xinhua; Yan, Hua; Wang, Lixian (Frontiers in Genetics, 2022)
Alternative splicing (AS) is a key step in the post-transcriptional regulation of gene expression that can affect intramuscular fat (IMF). In this study, longissimus dorsi muscles from 30 pigs in high- and low- IMF groups were used to perform Oxford Nanopore Technologies (ONT) full-length sequencing and Illumina strand-specific RNA-seq. A total of 43,688 full-length transcripts were identified, with 4,322 novel genes and 30,795 novel transcripts. Using AStalavista, a total of 14,728 AS events were detected in the longissimus dorsi muscle. About 17.79% of the genes produced splicing isoforms, in which exon skipping was the most frequent AS event. By analyzing the expression differences of mRNAs and splicing isoforms, we found that differentially expressed mRNAs with splicing isoforms could participate in skeletal muscle development and fatty acid metabolism, which might determine muscle-related traits. SERBP1, MYL1, TNNT3, and TNNT1 were identified with multiple splicing isoforms, with significant differences in expression. AS events occurring in IFI6 and GADD45G may cause significant differences in gene expression. Other AS events, such as ONT.15153.3, may regulate the function of ART1 by regulating the expression of different transcripts. Moreover, co-expression and protein-protein interaction (PPI) analysis indicated that several genes (MRPL27, AAR2, PYGM, PSMD4, SCNM1, and HNRNPDL) may be related to intramuscular fat. The splicing isoforms investigated in our research provide a reference for the study of alternative splicing regulation of intramuscular fat deposition.